TATA KELOLA KOLABORATIF DALAM PENANGGULANGAN KEMISKINAN DI KABUPATEN PINRANG - Abdul Rasyid Sahar; Roy Valiant Salomo (The Indonesian Journal of Public Administration (IJPA), 2018)
Abstract, In SDGs regime, collaborative partnership used to reduce poverty. The rise of collaborative governance discourse is just because an involvement of the multiple stakeholders in multiple organizations across multiple jurisdictions who has it’s own understanding of the problem and solution differently. In this paper, we examine the implementation of collaborative governance and it's affected factors in Pinrang's poverty alleviation. Since 2016, local government initiated The Poverty Reduction Department (Bagian Penanggulangan Kemiskinan) as a special board for eradicating poverty by an integrative framework for collaborative governance. This board intended to assist on the Regional Poverty Alleviation Coordination Team (TKPKD), to integrate a number of poverty alleviation program, and also to merge the database differences between The Central Statistics Agency (BPS) and TKPKD. However, while BPK has an important role to play, there are many conditions and settings that bother for driving progressively cyclical or iterative interactions between multiple stakeholders. In addition, the Pinrang poverty rate was increased in 2016 period. BPS announced that the number of people living below the poverty line was 256.054 in 2017 or 8,5 percent of the total population. This study argues that a lack of leadership and capacity buildings shape the prospects for and challenges of initiating and sustaining collaborative governance in Pinrang’s poverty alleviation program.Keywords: Collaborative Governance, Poverty Allevation Program, Local GovernmentAbstrak, Dalam rezim SDG’s, pendekatan untuk mengentaskan kemiskinan adalah collaborative partnership. Diskursus ini mengemuka karena kemiskinan merupakan isu multisektoral yang dinamis dan kompleks. Pemetaan solusinya pun merujuk pada pelibatan berbagai jenjang organisasi, multidispilin, dan lintas yurisdiksi. Penelitian ini akan meninjau penerapan dan faktor yang berpengaruh pada tata kelola kolaboratif dalam penanggulangan kemiskinan di Kabupaten Pinrang dengan menggunakan metode deskriptif analitis. Pada 2016, sebagai momentum reformasi birokrasi, Pemerintah Pinrang membentuk OPD yang khusus concern dalam menanggulangi kemiskinan melalui kerangka kolaboratif antar jenjang pemerintahan dan pihak non pemerintah untuk mangakomodasi peran TKPKD Pinrang yang tidak optimal, program kemiskinan yang tidak terintegrasi, dan perbedaan Basis Data Kemiskinan (BPS-TNP2K) yang menjadi rujukan pemerintah daerah. Namun demikian, meskipun penerapan tata kelola kolaboratif diarus utamakan dalam penanggulangan kemiskinan, tetapi belum sepenuhnya menjadi solusi alternatif terhadap tingkat kemiskinan daerah yang masih konsisten di angka 8,5%. Sampai pada tahun 2017, realisasi target angka kemiskinan Pinrang belum terwujud di angka 6%. Penelitian ini menemukan bahwa tidak optimalnya pembangunan dimensi trust dan mutual understanding sebagai salah satu komponen esensial, juga, kapasitas pemimpin kolaborasi menjadi variabel penentu menghambat proses kolaborasi ke tingkat yang lebih iteratif dan dinamis (collaborative dynamics).Kata kunci:    Collaborative Governance, Penanggulangan Kemiskinan, Pemerintahan Lokal